2021
DOI: 10.52725/aocl.2021.20.2.55
|View full text |Cite
|
Sign up to set email alerts
|

Refractive Outcomes after Primary Vitrectomy Combined with Cataract Surgery

Abstract: Purpose: To evaluate the tendency of refractive prediction error and to examine factors that affect the refractive changes after combined vitrectomy and cataract surgery. Methods: We retrospectively reviewed demographic and clinical data, including axial length, intraocular pressure (IOP), preoperative anterior chamber depth, target refraction, preoperative refraction, postoperative refraction, keratometry, and refractive prediction error (the difference between postoperative and target refraction) of a retina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Another strength of this study is the fact that we examined PE using three different formulae (SRK/T, Haigis, and SRK II) rather than using only one formula as in other previous studies [11][12][13][14][15][16]. We also analyzed PE at different timepoints of 1, 3, and 6 months post-operatively to identify any time-related changes.…”
Section: Kang Et Al Suggested Effective Lens Position (Elp) Shift As ...mentioning
confidence: 99%
See 2 more Smart Citations
“…Another strength of this study is the fact that we examined PE using three different formulae (SRK/T, Haigis, and SRK II) rather than using only one formula as in other previous studies [11][12][13][14][15][16]. We also analyzed PE at different timepoints of 1, 3, and 6 months post-operatively to identify any time-related changes.…”
Section: Kang Et Al Suggested Effective Lens Position (Elp) Shift As ...mentioning
confidence: 99%
“…It is cost-effective, reduces the number of necessary surgeries and improves intraoperative macula visualization by removing the opacified lens [4]. However, previous studies have reported that combined phacovitrectomy for ERM may result in myopic shift of the target postoperative refraction [10][11][12][13][14], but few studies were able to identify factors associated with such myopic shift [15,16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…공수정체가 앞으로 밀리면서 발생하는 것으로 보인다. [7][8][9][10][11][12] 백내장수술 단독 시행 시 인공수정체의 지지부 형태에 따 른 안정성을 비교한 연구가 있으며, 13,14 Xiao et al 13…”
unclassified